DEVELOPMENT OF A BILINGUAL WORKSHEET-BASED MATHEMATICS MODULE WITH REALISTIC MATHEMATICS EDUCATION (RME) APPROACH ON MATERIAL OF TWO-DIMENSIONAL FIGURE - Chairil Hikayat; Suparman Suparman (Universitas Ahmad Dahlan, 2019)
This study's background was students who were less independent and still had difficulties in solving abstract things. The purpose of this study was to develop a module with the RME approach so that students would get a better understanding of the concept of the material being taught, especially on the two-dimensional figure. To identify the module's feasibility was based on the assessment of material experts, media experts, and student responses to the modules that have been made. The study was conducted using the Research and Development (R & D) method. The steps include (1) potential and problems, (2) data acquisition, (3) product design, (4 design validations, (5) design improvements, (6) product trials, (7) product revisions, (8 ) usage test Subjects of the trial included: (a) product review experts, (b) education practitioners, (c) Class VII junior high school students. Development of modules included: (a) gathering information, (b) module design, (c) validate the material expert, (d) product revision. The next step is the feasibility of the module, which includes: (a) validation by experts, (b) expert revision, (c) product trial, (d) revision I, (e) test try usage, (f) revision II.Â Data collection techniques are interviews and questionnaires. Types of data used quantitative and qualitative data. This study uses qualitative descriptive analysis, which is converted into quantitative values based on the Likert scale. The study results indicated that the study successfully developed the mathematics learning module on the two-dimensional figure for the second semester's seventh-grade students with the RME approach. The results of the study by material experts obtained an average score of 201 with an outstanding category. The results of the assessment by media experts obtained an average score of 129 with very good categories. Student response results to the module included in the good category with an average score of 89.3. These results indicated that the mathematics learning module on the two-dimensional figure for the seventh-grade junior high school students was feasible and effective in the learning process.